MTORC2 Regulates Lipogenic Gene Expression through PPARγ to Control Lipid Synthesis in Bovine Mammary Epithelial Cells. (16th May 2019) - Guo, Zhixin; Zhao, Keyu; Feng, Xue; Yan, Dandan; Yao, Ruiyuan; Chen, Yuhao; Bao, Lili; Wang, Zhigang
Abstract : The mechanistic target of rapamycin complex 2 (mTORC2) primarily functions as an effector of insulin/PI3K signaling to regulate cell proliferation and is associated with cell metabolism. However, the function of mTORC2 in lipid metabolism is not well understood. In the present study, mTORC2 was inactivated by the ATP-competitive mTOR inhibitor AZD8055 or shRNA targeting RICTOR in primary bovine mammary epithelial cells (pBMECs). MTT assay was performed to examine the effect of AZD8055 on cell proliferation. ELISA assay and GC-MS analysis were used to determine the content of lipid. The mRNA and protein expression levels were investigated by RT/real-time PCR and western blot analysis, respectively. We found that cell proliferation, mTORC2 activation, and lipid secretion were inhibited by AZD8055. RICTOR was knocked down and mTORC2 activation was specifically attenuated by the shRNA. Compared to control cells, the expression of the transcription factor gene PPARG and the lipogenic genes LPIN1, DGAT1, ACACA, and FASN was downregulated in RICTOR silencing cells. As a result, the content of intracellular triacylglycerol (TAG), palmitic acid (PA), docosahexaenoic acid (DHA), and other 16 types of fatty acid was decreased in the treated cells; the accumulation of TAG, PA, and DHA in cell culture medium was also reduced. Overall, mTORC2 plays a critical role in regulating lipogenic gene expression, lipid synthesis, and secretion in pBMECs, and this process probably is through PPAR γ . This finding provides a model by which lipogenesis is regulated in pBMECs.